Poetry in the workplace: Bill Murray’s public reading as an applied art form - Sebestyén, Attila (AMERICANA E-journal of American Studies in Hungary, 2018)
My paper supports the claim that the mind-forming effects of poetry can be utilized in the areas of business activities or workplace life. For managers and employees, literary reading may become a playground which provides them with various possibilities, outside the rules of their own areas, for mind-liberating connections among different worldviews. According to previous reference works, even businesspeople themselves affirmed: poetry creates possibilities for them to view the world from other people’s perspectives. That could become important in business life and workplaces because one of the central dilemmas of contemporary discourse about management and corporate culture is the challenge of tolerating ambiguities, uncertainties, and conflicts (that is the task of managing various meanings).